The legal instrument of protecting traditional cultural expressions ownership in intellectual property rights law - Widyanti, Yenny Eta (Technium Social Sciences Journal, 2021)
Indonesia grows with its tribal and cultural diversity. Traditional Cultural Expressions are present as part of the cultural asset of a highly valued state’s legacy, which, on the contrary, is prone to misappropriation by other countries. Departing from this weakness, normative legal research is used to analyse the significance of instrument to protect the ownership of Traditional Cultural Expressions in the perspective of Intellectual Property Rights Law by employing statutory and conceptual approach. The legal materials involve primary and secondary data obtained and analysed normatively to investigate the perspective of the issue studied. The research result reveals that the protection for the ownership constitutes both positive and defensive protection, where the former is represented by the enforcement of rules of law, either through ratification of international conventions in national law or through the regulations concerning the protection of Traditional Cultural Expressions that also take legislation in the process, while the defensive protection involves inventory and documentation of the TCEs as part of preservation, safeguarding, and promotion, aimed to maintain the existence of the cultural heritage of the state.